Penanaman Karakter Kerja Keras Dalam Pembelajaran Matematika Pada Siswa Kelas VII Sekolah Menengah Pertama (SMP) Al-Firdaus Tahun Pelajaran 2015/2016 - Nur Aini, Ovi Dianah, Dr. Sumardi, M.Si (2016)
Singer study aims to describe the review process work hard hearts planting character learning mathematics on seventh grade students of SMP Al-Firdaus. Being a singer process divided prayer section, that is before and learning of mathematics lasted long. Singer Research using qualitative approaches by type descriptive study. Data collection techniques with methods observation, interview and ocumentation. Checking the validity of the data using triangulation techniques methods and resources. Namely with triangulation method to compare the findings of bservation, interview and documentation. While riangulation resources conducted comparing the results interview with lesson teachers, students and teachers in foster care. Analysis Data with stage presentation of data reduction and withdrawal conclusion. Its popularity has conducted research, hard work character investment process hearts learning math can be done with: 1. Providing an understanding shown to students importance and benefits of hard work to review themselves 2. Teach shown to students that hard work is important to review that achieve results the findings maximum 3. Preparing physical and sychological condition before student learning math start 4. Provide exercises shown to students sustainable operations 5. Provide motivation that led to a review would work hard.